2020
DOI: 10.1177/1055665619900871
|View full text |Cite
|
Sign up to set email alerts
|

Defining Risk of Postoperative Obstructive Sleep Apnea in Patients With 22q11.2DS Undergoing Pharyngeal Flap Surgery for Velopharyngeal Dysfunction Using Polysomnographic Evaluation

Abstract: Objective: To determine pre- and postoperative prevalence of obstructive sleep apnea (OSA) in patients with 22q11.2 deletion syndrome (DS) undergoing wide posterior pharyngeal flap (PPF) surgery for velopharyngeal dysfunction (VPD). Design: Retrospective study using pre- and postoperative polysomnography (PSG) to determine prevalence of OSA. Medical records were reviewed for patients’ medical comorbidities. Parents were surveyed about snoring. Setting: Academic tertiary care pediatric hospital. Patients: Forty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…A staged tonsillectomy with or without adenoidectomy can be performed a few months prior to speech surgery. This procedure is often recommended to make more space in the airway prior to the speech surgery in the hope of limiting the risk of postoperative OSA following speech surgery [ 13 ]. Additionally, in some cases, tonsillectomy is needed to allow access to the surgical site(s) for the speech surgery [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A staged tonsillectomy with or without adenoidectomy can be performed a few months prior to speech surgery. This procedure is often recommended to make more space in the airway prior to the speech surgery in the hope of limiting the risk of postoperative OSA following speech surgery [ 13 ]. Additionally, in some cases, tonsillectomy is needed to allow access to the surgical site(s) for the speech surgery [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…This procedure is often recommended to make more space in the airway prior to the speech surgery in the hope of limiting the risk of postoperative OSA following speech surgery [ 13 ]. Additionally, in some cases, tonsillectomy is needed to allow access to the surgical site(s) for the speech surgery [ 13 ]. In this study, airway optimization prior to speech surgery was indicated for 64% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations